Quality Assurance Practices by the Administrators of the Association of Local Colleges and Universities in CAMANAVA - Atienza, Atienza; Atienza, Shyla Ramos-; Aquino, Abner (International Journal of Management and Education in Human Development, 2024)
This research investigates the effectiveness of quality assurance measures implemented by administrators in the CAMANAVA's Association of Local Colleges and Universities (ALCU). CAMANAVA Area is composed of the cities of Caloocan, Malabon, Navotas, and Valenzuela, located in the northern part of Metro Manila, Philippines. The study examines four key areas in quality assurance: analysis, design and development, implementation, and evaluation, seeking correlations among them. Using a quantitative approach, the study analyzes administrators' demographics, assesses the effectiveness of quality assurance practices, identifies any significant relationships among these practices, and suggests solutions to encountered challenges. Data were gathered through a questionnaire survey involving 68 administrators from various member institutions. Findings reveal that administrators are predominantly male, married, in their forties and fifties, with varying educational backgrounds, and mostly serving as department chairs for less than ten years. Agreement levels varied across different aspects of quality assurance practices, with emphasis on curriculum classification, instructional program clarity, and formative evaluation by department chairs. Design and development focused on course objective identification, while implementation centered on communicating performance standards, with discrepancies in activities such as peer coaching. Evaluation parameters showed strong agreement on identifying summative evaluation goals but gaps in execution. Correlation analysis indicates strong positive relationships between various phases of quality assurance practices, particularly between design and implementation, and implementation and evaluation. Identified problems mainly revolve around curriculum, instruction, faculty, and student-related issues,with summative evaluation goals and student competencies being significant concerns. Proposed solutions include recognizing curriculum programs, effective communication of performance standards, and addressing student needs.